Multi-spectroscopic investigation on the spatial distribution and copper binding ability of sediment dissolved organic matter in Nansi Lake, China - Ren, Haoyu; Ma, Feiyang; Yao, Xin; Shao, Keqiang; Yang, Liwei (Journal of hydrology (Amsterdam), 2020)
[Display omitted] •Spectral properties and Cu-binding properties of DOM collected from the upper lake and lower lake in Nansi Lake were studied.•Humic-/fulvic-like substances were the main substance of DOM collected from Nansi Lake.•Protein-like components exhibited higher Cu (II) binding abilities than humic-/fulvic-like ones.•Interactions of Cu2+ with DOM were probably affected by submerged plants and the water conservancy projects. Interaction between dissolved organic matter (DOM) and heavy metals have been widely studied, and the differences in DOM properties have a great impact on the capacity of DOM-metals binding. In this study, the samples were collected from the upper lake and lower lake in Nansi Lake, respectively. According to the ratio of the fluorescence intensity of component to the total fluorescence intensity (%Fmax) in the two areas, obvious differences were found in the properties of DOM. The content of humic-like substances showed a decreasing trend from the north to south in Nansi Lake. On this basis, samples from north and south ends of Nansi Lake were selected for fluorescence titration. All components were quenched with the increasing of Cu2+ addition. Combining the results of Synchronous fluorescence (SF) spectra with two-dimensional correlation spectroscopy (2D-COS), fluorescent quenching near 275 nm was quicker than the changes that occurred at the wavelength that after 275 nm, which suggested that the complexation occurred firstly for protein-like components as compared with humic-like components. The modified Stern-Volmer model suggested that protein-like components had larger effective quenching constants (logKa = 3.47 ± 0.13 for component C5 in the upper lake and logKa = 3.57 ± 0.19 for component C4 in the lower lake) than humic-like components and it is not affected by the region, indicating that protein-like substances might have a higher metal binding potential than humic-like substances in Nansi Lake. The binding constants and the binding sites suggested that humic-like components also had a nonnegligible binding potential in Nansi Lake although the protein-like components revealed a stronger binding ability in fluorescence quenching.